Application of Fuzzy Linear Programming Model in Agricultural Economic Management - Wang, Yuping (Journal of mathematics (Hidawi), 2022)
Fuzzy linear programming has a wide range of applications in agricultural economic management. In this paper, the mathematical model of fuzzy linear programming was studied in detail, and then under the restriction of elastic constraints, the f(ti) and g(t0) function expressions and their optimal solutions were obtained. Subsequently, the fuzzy linear programming was applied to the agricultural economic management of the five urban areas of Zhengzhou, and its applicability was studied. The results showed that the f(ti) and g(t0) function expressions obtained by different stretch degrees were not the same, and both had a unique optimal solution. In addition, the mathematical model based on fuzzy linear programming could well predict the pull force in agricultural economic management, so as to provide theoretical support for the application of fuzzy linear programming.